Challenges in Implementing Human Rights Court Rulings in Indonesia: From Theory to Practice (Indonesian Court and Justice Review, 2024)
Despite Indonesia’s commitment to human rights through its legal framework and ratification of international conventions, the practical implementation of human rights court rulings often faces significant challenges. This study investigates the gap between the theoretical foundations of human rights protections in Indonesia and their real-world application, focusing specifically on the difficulties encountered in implementing rulings made by human rights courts. By analyzing a combination of case studies, legal texts, and interviews with legal experts, practitioners, and affected individuals, the research explores systemic issues such as political interference, institutional inertia, lack of enforcement mechanisms, and limited public awareness. The findings reveal that while human rights rulings may be issued in accordance with national laws and international human rights standards, their actual enforcement is often delayed or obstructed by weak institutional capacity, insufficient political will, and a lack of effective coordination among various government agencies. The study’s novelty lies in its detailed examination of both the theoretical and practical dimensions of human rights court rulings in Indonesia, providing a comprehensive view of the implementation challenges. The urgency of this issue is underscored by the need to strengthen judicial independence and promote greater accountability within the legal system. This research contributes to the broader discourse on human rights enforcement, offering recommendations for reforming the legal infrastructure and improving the efficiency of implementing human rights decisions